2016
DOI: 10.5430/cns.v4n4p46
|View full text |Cite
|
Sign up to set email alerts
|

Responses after participating in Family Health Conversations in families with a family member who has suffered a stroke: A mixed methods research study

Abstract: Background: It has been proposed that support for families in which a family member has suffered a stroke should involve the whole family system. Aim: The aim was to evaluate the responses of Family Health Conversation (FamHC) in families with a member under the age of 65 who has been diagnosed with stroke. Methods: In this mixed methods research study, families were included in an intervention group and in a control group. For both groups pre-and post-intervention quantitative data was collected and for the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Presumably this was because of the trusting environment that FamHCs provided, as previously found by Dorell, Bäckström, et al. (2016) and Sundin et al. (2016) .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Presumably this was because of the trusting environment that FamHCs provided, as previously found by Dorell, Bäckström, et al. (2016) and Sundin et al. (2016) .…”
Section: Discussionmentioning
confidence: 61%
“…Although the responses in the questionnaires are based on few respondents, the posttest responses showed a tendency for families, in particular the patients, to experience increased support from RNs. Presumably this was because of the trusting environment that FamHCs provided, as previously found by Dorell, Ba¨ckstro¨m, et al (2016) and Sundin et al (2016). For some family caregivers, it was the first time they had been included in a conversation with the RN in the HF clinic and given the chance to talk about their caregiving situation.…”
Section: Families' and Rns' Experiences Of Famhcsmentioning
confidence: 90%
See 1 more Smart Citation
“…Also, previous studies have shown that families participating in FamHC have improved insight, understanding and communication. Thus, negative feelings could be expressed openly and reflected upon within the family (17,(31)(32)(33)(34)(35). Also, a study by Sundin et al (36) shows that family members share their beliefs and talk about serious issues.…”
Section: Discussionmentioning
confidence: 99%
“…When viewing the family from a systemic approach, a patient should not be considered isolated, but instead as a part of a system where all the family members’ behaviours and beliefs affect each other. A variety of practices based on FSN have been scientifically evaluated with positive outcomes on family health and well‐being in different healthcare contexts both in Sweden (e.g., Benzein, Olin, & Persson, ; Persson & Benzein, ; Sundin et al, ) and internationally (e.g., Duhamel, Dupuis, Turcotte, Martinez, & Goudreau, ; Sveinbjarnardottir, Svavarsdottir, & Wright, ).…”
Section: Introductionmentioning
confidence: 99%